Pengaruh Model POE (Predict-Observe-Explain) Berbantuan Media Diorama Terhadap Hasil Belajar IPAS Kelas V - Marbun, Putri Elisa (Jurnal Riset Pendidikan Dasar (JRPD), 2025)
The problem in this research is the low learning outcomes of students IPAS in grade V. This research aims to examine the influence of the POE (Predict-Observe-Explain) model assisted by diorama media on students' learning outcomes. The research uses a quantitative method with a quasi-experimental design. The population consists of 50 students from classes VA and VB. The instrument is a learning outcome test with 20 multiple-choice questions, validated for reliability, difficulty, and differentiation. Results show the experimental class scored an average of 79.60, while the control class scored 61.80. a Sig. (2-tailed) value of 0.001. Since 0.001<0.05 ditetapkan = > 2,010with a significance level of 5% (), leading to the rejection of Hâ‚€ and acceptance of Hâ‚. It concludes that the POE model with diorama media significantly affects the IPAS outcomes of grade V students at SDN 101832 Pancur Batu.